1948
DOI: 10.1172/jci101931
|View full text |Cite
|
Sign up to set email alerts
|

DEPRESSION OF THE EXOGENOUS CREATININE/INULIN OR THIOSULFATE CLEARANCE RATIOS IN MAN BY DIODRAST AND p-AMINOHIPPURIC ACID 1

Abstract: Exogenous creatinine is excreted by the renal tubules of the aglomerular fish (1 to 4), the glomerular dogfish (5, 6), teleost (7) and chicken (8), but not by the frog (9), turtle (10), dog (11 to 14), sheep (15), seal (16), rabbit (17) or cat (18). Among the mammals tubular excretion is recorded only in the anthropoid apes (19,20) and man (21).The evidence for tubular excretion in man, as initially advanced by Shannon, consists of the facts that (1) the exogenous creatinine/inulin clearance ratio exceeds 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

1948
1948
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…As facilities for inulin or mannitol clearances were not available, creatinine clearance was used as a reflection of glomerular filtration, although it is generally felt that inulin or mannitol better measure this in man (31,32). Creatinine/inulin ratios recently published (33,34) suggest, however, that creatinine clearance is a fairly good measure of glomerular filtration, especially when PAH or diodrast is administered concurrently.…”
Section: Methodsmentioning
confidence: 99%
“…As facilities for inulin or mannitol clearances were not available, creatinine clearance was used as a reflection of glomerular filtration, although it is generally felt that inulin or mannitol better measure this in man (31,32). Creatinine/inulin ratios recently published (33,34) suggest, however, that creatinine clearance is a fairly good measure of glomerular filtration, especially when PAH or diodrast is administered concurrently.…”
Section: Methodsmentioning
confidence: 99%
“…Using the single injection method, they found that the thiosulphate/ inulin clearance ratio fell within the range of 0.7 to 1.3 (average 0.99 + 0.08) and that this ratio was independent of the plasma concentration between 6 and 60 mg. per 100 cc. The apparent identity of these clearances has been confirmed by Brun (3), Crawford (4), and Blegen, Qrning, and Aas (5), while Bj0rnboe, Dalgaard-Mikkelsen, and Raaschou (6) report that in three subjects the thiosulphate/inulin clearance ratio is higher when the urine is alkaline than when it is acid.…”
mentioning
confidence: 86%
“…This occurred at physiological (9) as well as increased creatinine plasma levels (14,17). Similarly, studies in humans, dogs, and chicken revealed that organic anions can inhibit renal creatinine secretion (5,8,27,29). Moreover, while cimetidine inhibits OCT, it can also inhibit transport mediated by OAT1 and OAT3 (1,6,19), and basolateral uptake of cimetidine is additively blocked by probenecid and tetraethylammonium, blockers of organic anion and cation transporters, respectively (15,36,38).…”
mentioning
confidence: 93%